2015
DOI: 10.1902/jop.2015.140467
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Systemic Vitamin K2 and Vitamin D3 on Gingival Inflammation and Alveolar Bone in Rats With Experimentally Induced Periodontitis

Abstract: Within the limitations of this study, vitamin D3 and K2 alone or in combination did not affect gingival IL-1β and IL-10, serum B-ALP and TRAP-5b levels, or alveolar bone compared with conventional periodontal therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
3
20
0
1
Order By: Relevance
“…The findings of the present study are in accordance with Aral, et al 3 (2015), which also demonstrated that vitamin D3 and vitamin K2 supplementation were not effective in the reduction of alveolar bone resorption in rats with experimentally induced periodontitis. Conversely, Hong, et al 13 (2015) recently demonstrated in dogs that vitamin D3 and calcium supplementation during the early stage of socket healing promoted accelerate bone regeneration, improving new bone formation, bone density, and reducing the extent of vertical ridge resorption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study are in accordance with Aral, et al 3 (2015), which also demonstrated that vitamin D3 and vitamin K2 supplementation were not effective in the reduction of alveolar bone resorption in rats with experimentally induced periodontitis. Conversely, Hong, et al 13 (2015) recently demonstrated in dogs that vitamin D3 and calcium supplementation during the early stage of socket healing promoted accelerate bone regeneration, improving new bone formation, bone density, and reducing the extent of vertical ridge resorption.…”
Section: Discussionsupporting
confidence: 92%
“…Because trabecular bone contains marrow cavities, the BV/TV should be <100%. The VOI corresponded to dilatation of the implant shape of 25 voxels: the inners 5 layers of voxels were discarded to avoid the artifacts observed in this region, resulting in a VOI of 7.933 mm 3 , and the top of the VOI was placed on the implant neck. The BIC was also calculated in outside of these 5 layers of voxels.…”
Section: Methodsmentioning
confidence: 99%
“…No significant differences were seen in the gingival contents of IL-1β and IL-10, blood B-ALP, TRAP-5b, and calcium, nor in alveolar bone mass between the groups receiving SRP and vitamins, and the experimental group receiving SRP alone. Furthermore, vitamin D3 and K2 alone, or combined, failed to affect gingival levels ofIL-1β and IL-10, as well as blood B-ALP and TRAP-5b, or the alveolar bone mass, as compared with traditional periodontal treatment per se [52].…”
Section: Some Recent Articles "Establishing" the Vitamin K2 Effect Onmentioning
confidence: 89%
“…We, therefore, think that there is a significant positive correlation between the presence of periodontal disease and low intake of magnesium in not only the elderly but also in young adults. Both animal and human studies have reported that a lack of calcium intake leads to alveolar bone resorption [34, 35] and a decrease in bone density [36], indicating that insufficient calcium intake might cause the progression of periodontal disease. In addition, it was shown that the risk of periodontal disease associated with calcium intake was observed in both men and women aged between 20 and 39 years (odds ratio; 1.99 and 1.84), only in men aged between 40 and 59 years, and in neither men nor women aged ≥60 years [37].…”
Section: Discussionmentioning
confidence: 99%